Fabrication of an ultrathin PEG-modified PEDOT:PSS HTL for high-efficiency Sn–Pb perovskite solar cells by an eco-friendly solvent etching technique. Issue 13 (16th March 2023) - Guo, Pengju; Dong, Jun; Xu, Cunyun; Yao, Yanqing; You, Jiayu; Bian, Hongyu; Zeng, Wenqi; Zhou, Guangdong; He, Xiaofeng; Wang, Meng; Zhou, Xianju; Wang, Min; et al.
Abstract : We have creatively introduced an eco-friendly solvent etching techniques to prepare ultra-thin PEDOT:PSS layers modified with PEG. The PCE of Sn–Pb PSCs using PEG-PEDOT:PSS HTL is increased from 20.52% to 21.58%, and the stability of the device is also improved. Abstract : Poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is widely used as a hole transport layer (HTL) in inverted perovskite solar cells (PSCs) because of its excellent hole transport capability and simple preparation process. According to theoretical studies, a thinner PEDOT:PSS HTL allows more incident light to enter the perovskite layer. However, the PEDOT:PSS HTL prepared by the traditional deposition process has some limitations, such as the thick HTL, abundant defects at the PEDOT:PSS/perovskite interface, etc. Is there a preparation process that can achieve the thinning and modification of the PEDOT:PSS HTL in one-step process at the same time? In this work, inspired by the semiconductor etching process, an eco-friendly solvent etching technique is applied during the spin-coating process to fabricate an ultrathin PEDOT:PSS HTL and simultaneously introduce a green passivator (polyethylene glycol, PEG) as the bridge molecule on the HTL upper surface. In this process, the green PEG aqueous etchant can etch the excess bulk PEDOT:PSS away to form an ultrathin PEDOT:PSS HTL with PEG molecules and rich PEDOT domains remained on its surface (PEG-PEDOT:PSS HTL). This well-designed HTL is successfully thinned to enhance its light transmission and can be better matched with the Sn–Pb perovskite layer. As a result, the power conversion efficiency of Sn–Pb PSCs using the PEG-PEDOT:PSS HTL is improved from 20.52% of the reference to 21.58%, and the stability of Sn–Pb PSCs is dramatically enhanced as well.